Frantz's Tumor: Report of a case - Macedo, Thiago Andrade de (2004)
Frantz´s tumor is a rare neoplasia of the pancreas that occur mainly in teenage patients with a good prognosis. A little over 300 cases have been reported in the literature worldwide. The autors present a case of Frantz's tumor on a female patient, whose presentation was palpable abdominal mass. CT scans and ultrasound imaging showed a solid cystic mass. Two thirds of these tumors occur at the body or tail of the pancreas, and in spite of the excessive growth around the pancreas, it rarely invades vascular structures or adjacent organs, what could have been seen intraoperatively in this case. The patient was submitted to a partial pancreatectomy of body and tail with preservation of the spleen. Microscopic examination displayed evident cystic cavities with occasional papillary structures. The patient is disease-free 24 months after the operation. We emphasize the need to consider tumor of Frantz as a differential diagnosis for abdominal masses in youngsters.